Does the Route of Cocaine Use Affect the Mortality and Outcomes of Cocaine-Induced Intestinal Ischemia? A Systematic Review. (October 2021) - Farooq, Umer; Gondal, Amlish B.; Susheela, Ammu; Tarar, Zahid Ijaz; Malik, Adnan; Zafar, Muhammad Usman; Sharif, Aftab; Ghous, Ghulam
Intestinal ischemia results from diminished perfusion of the colon resulting in tissue hypoxia. Anecdotal reports suggest that cocaine-induced intestinal ischemia has the highest mortality and longer length of stay among the vasoconstrictors. The present study aimed to summarize the available studies in the literature to assess the effect of routes of consumption on the outcomes of cocaine-induced intestinal ischemia. We conducted a systematic search of MEDLINE from inception through October 2019. Studies of cocaine-induced intestinal ischemia were included if data were available on comorbidities, mortality, and hospital length of stay (LOS). The study's primary outcomes were mortality and need for surgery, while secondary outcomes included the hospital length of stay, LACE index, and hospital score. Statistical tests used included linear and binary logistic regression. STATA 2015 was used, and P < 0.05 was statistically significant. Of the 304 studies, 8 case series and 45 case reports (n = 69 patients) met the inclusion criteria. Different routes of cocaine use had similar mortality odds and the need for surgery for intestinal ischemia. Hospital LOS showed significant difference among the subgroups. Readmission scores (LACE and hospital score) were higher for intravenous and smoking than ingestion and intranasal use ( P < 0.05). In conclusion, different routes of cocaine use appear to have similar mortality odds for intestinal ischemia, which vary significantly among the different routes of cocaine consumption for the length of stay and readmission scores. Prompt recognition of the route of cocaine use is vital to improve the outcome. Large-scale and well-designed observational studies are needed to investigate this topic further.